Kompos Tandan Kosong Kelapa Sawit dengan penambahan Kotoran Sapi dan Berbagai Bioaktivator - Fitra Gustiar; Imam Wibisono; Munandar Munandar (Jurnal Riset Agribisnis dan Peternakan, 2020)
Palm oil processing in addition to producing the main products of Curve Palm Oil (CPO) and core oil will also produce 46.5% of which will produce solid waste, in the form of empty bunches, curved, palm mud and fiber. One solution to overcome this waste is by making empty fruit bunches into organic fertilizer. Oil palm empty fruit bunches are difficult to decompose, because OPEFB consists mainly of 45.9% cellulose and 22.8% lignin, which is difficult to decompose. Various ways to accelerate decomposition by adding organic material (cow dung) and Bioctivator. This research was conducted to obtain the optimal composition between empty bunches and cow dung as compost material with various bioactivators. This research was conducted with a completely randomized design factorial with 3 repetitions, treatment of a combination of the ratio of OPEFB and Cow Dung. 100%OPEFB + 0% Cattle Dung, 90%OPEFB + 10% Cattle Dung, 70 % OPEFB + 30% Cattle Dung, 60% OPEFB + 40% Cattle Dung, with factorial administration of biofetallic bioactivators, BeKa, Tricoderma, Sp. The parameters observed in this study in the first experiment included 1) Changes in the temperature of the compost process, 2) Changes in compost pH, 3) Compost color and texture, 4) Compost yield, 5) C-Organic, 6) N-Total, 7 ) C / N ratio. Measuring compost temperature showed that in all treatments there was a significant increase in temperature between 48.0 °C to 49.68 °C. The color indicator in the treatment without the addition of cow manure will appear black but in the texture of the compost material the treatment with no cow manure will be more rough, while the results of laboratory analysis shows a ratio of 90% OPEFB + 10% cow dung will show better results due to closer to SNI compost organic fertilizer standards, and biofetallic treatment showed the highest N-total content.